REJECTION CHARACTERISTICS OF ORGANOCHLORINE PESTICIDES BY LOW PRESSURE REVERSE OSMOSIS MEMBRANE - Utami, Woro Nastiti; Iqbal, Rofiq; Wenten, I Gede (Center for Environmental Technology, 2010)
TheÃ‚Â increasedÃ‚Â useÃ‚Â ofÃ‚Â pesticidesÃ‚Â hasÃ‚Â ledÃ‚Â to manyÃ‚Â benefitsÃ‚Â suchÃ‚Â asÃ‚Â advancedÃ‚Â productivity and lower maintenance costsÃ‚Â in agriculture. On the other hand, theirÃ‚Â adverseÃ‚Â effectsÃ‚Â haveÃ‚Â alsoÃ‚Â grown : an increase ofÃ‚Â the risks to the ecosystem and human health. Pressure driven technique such as reverse osmosis and nanofiltration have the potentiality to remove hazardous organic micropollutants such as pesticides. The rejection characteristic of artificial water with 10 ppb concentration of endosulfan and organochlorine pesticides from upper Citarum water shed sample were investigated with a commercial low pressure reverse osmosis unit on laboratory scale. Rejection and flux were measured with a varied operational parameters ; pH, pressure, and feed concentration. Endosulfan rejection was achieved > 80% with all varied operational parameters. There was a little dependence permeate flux and percent of rejection on pH. An increasing pressure caused a higher permeate flux while there was no effect of an increasing pressure to higher percentage of endosulfan rejection. An increasing feed concentration caused a lower permeate flux due to an increasing osmotic pressure.Ã‚Â An increasing feed concentration also result in an increasing percent of endosulfan rejection. Organochlorine pesticides found in river water sample which are lindane, aldrin, and heptachlor were all rejected 100%. This may be caused by natural organic matter present in river water and hydrophobicity. Percent rejection was constant to pressure and pH variation.Ã‚Â Keywords : Low Pressure Reverse Osmosis, Organochlorine Pesticides, Pressure, pH, Feed Concentration